2022
DOI: 10.1007/s10722-022-01450-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity and population structure in local alfalfa genotypes using iPBS molecular markers

Abstract: iPBS retrotransposon markers, in other words, inter-primer binding site markers based on retrotransposon, have been useful for the determination of genetic diversity in several plants. The study was evaluated by using 10 iPBS molecular markers the level of genetic diversity and genetic structure of alfalfa genotypes. A total of 280 alleles in 50 alfalfa genotypes (48 local genotypes and 2 commercial varieties) were obtained by 267 polymorphic markers with an average of 28 per locus, ranging from 9 to 41 allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
8
1
Order By: Relevance
“…Notably, the H value obtained in this study surpasses those reported in earlier wheat research utilizing iPBS markers for characterization [11]. Additionally, Shannon information index (I) value (0.31) and the effective number of alleles (Ne, 1.48) observed in this research exceed the values reported in previous studies of various plant species employing iPBS markers [11,37,50]. The heightened values observed for several diversity indices in this research may be attributed to variations in germplasm and the characteristics of the employed molecular marker [11].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Notably, the H value obtained in this study surpasses those reported in earlier wheat research utilizing iPBS markers for characterization [11]. Additionally, Shannon information index (I) value (0.31) and the effective number of alleles (Ne, 1.48) observed in this research exceed the values reported in previous studies of various plant species employing iPBS markers [11,37,50]. The heightened values observed for several diversity indices in this research may be attributed to variations in germplasm and the characteristics of the employed molecular marker [11].…”
Section: Discussioncontrasting
confidence: 73%
“…Using the COPH module, the cophenetic value matrix was initially computed by using the tree matrix that was obtained from the iPBS analysis. The MXCOMP module was used to investigate the goodness-of-fit value (r) representing the relationship between the UPGMA dendrogram and the Dice similarity index matrix [37]. To undertake an analysis of the population structure of wheat varieties, STRUCTURE version 2.3.4 was utilized [38].…”
Section: Ipbs Data Scoring and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Acharya et al [22] reported a high and stable improvement of dry matter yield in alfalfa genetic materials that may be utilized in order to develop high performing and well-adopted alfalfa cultivars. Eren et al [23] analyzed alfalfa genetic diversity and local population structure by molecular markers. They concluded that the iPBS molecular markers can be a helpful tool in identifying parents with high genetic diversity in alfalfa breeding.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the adaptation of alfalfa subspecies to different geographies and climatic conditions, it has been observed that they differentiate from each other on the basis of population or subpopulation over time (Şakiroğlu et al 2015). Therefore, it is critical to evaluate and compare populations in terms of alfalfa populations grown in different geographies (İlhan, 2018a;Eren et al 2022). Agriculture 2022; 5 (2) 50-56 https://dergipark.org.tr/tr/pub/ja 51 Molecular markers, and especially next-generation sequencing technologies, serve as useful tools to determine population structures and divergences in alfalfa.…”
Section: Introductionmentioning
confidence: 99%